PENGARUH VIDEO KETELADANAN PADA KANAL YOUTUBE TERHADAP PERTUMBUHAN KARAKTER PESERTA DIDIK DI SEKOLAH DASAR - Anita Khoerunnisa Rianto; Dea Annisa; Rheina Putri Armesya Pasha; Arita Marini (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
Character building since children are in elementary school is very important to do, because children experience physical, social, emotional and spiritual growth, which will impact their lives in the future, so the formation of character based on exemplary and habituation is important to apply to student. This article was created to address the educational problems of elementary school children in carrying out a learning process that promotes character growth by not forgetting student academic development and being adapted to technological developments. This study uses a qualitative approach with literature study techniques or literature studies from various sources in the form of books, national journals, and research articles. The results of this study conclude that the use of exemplary videos in learning is a strategy that is quite appropriate for teachers to carry out, apart from being relevant to the all-digital era. The use of exemplary videos is also able to become an intermediary for teachers in giving concrete examples of positive attitudes to students so that they can eliminate mere verbalism.